Proceedings of the 8th Workshop on Asian Translation (WAT2021) 2021
DOI: 10.18653/v1/2021.wat-1.18
|View full text |Cite
|
Sign up to set email alerts
|

IITP at WAT 2021: System description for English-Hindi Multimodal Translation Task

Abstract: Neural Machine Translation (NMT) is a predominant machine translation technology nowadays because of its end-to-end trainable flexibility. However, NMT still struggles to translate properly in low-resource settings specifically on distant language pairs. One way to overcome this is to use the information from other modalities if available. The idea is that despite differences in languages, both the source and target language speakers see the same thing and the visual representation of both the source and targe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…It was observed that using text-based pre-trained models achieved better results for Hindi VG Test set compared to the multimodal model trained only on multimodal dataset [21]. However, it obtained lower results for the Challenge set.…”
Section: Multimodal Translation On Indian Languagesmentioning
confidence: 99%
“…It was observed that using text-based pre-trained models achieved better results for Hindi VG Test set compared to the multimodal model trained only on multimodal dataset [21]. However, it obtained lower results for the Challenge set.…”
Section: Multimodal Translation On Indian Languagesmentioning
confidence: 99%
“…Dentro de los modelos relacionados directamente con la búsqueda y recuperación de información tenemos el reporte de anteligencia artificial para tareas de asistencia legal compartida [16]; este trabajo basado en el sistema penal Indiano utilizando:…”
unclassified